2009
DOI: 10.1038/nrmicro2235
|View full text |Cite
|
Sign up to set email alerts
|

Explaining microbial population genomics through phage predation

Abstract: The remarkable diversity of genes within the pool of prokaryotic genomes belonging to the same species or pan-genome is difficult to reconcile with the widely accepted paradigm which asserts that periodic selection within bacterial populations would regularly purge genomic diversity by clonal replacement. Recent evidence from metagenomics indicates that even within a single sample a large diversity of genomes can be present for a single species. We have found that much of the differential gene content affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
356
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(396 citation statements)
references
References 66 publications
30
356
1
Order By: Relevance
“…These results could be attributable to different kinetics of the Tfd enzymes, e.g., enzymes with high versus low affinity for the substrate, or differential bacteriophage or protozoan predation of the abundant populations. The differential predation scenario has been well documented several times (33,(52)(53)(54), and preliminary findings reported by this study (discussed below) indicated that differential phage predation may be occurring in our mesocosms. However, whether or not this scenario fully applies to our mesocosm incubations remains to be experimentally tested.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results could be attributable to different kinetics of the Tfd enzymes, e.g., enzymes with high versus low affinity for the substrate, or differential bacteriophage or protozoan predation of the abundant populations. The differential predation scenario has been well documented several times (33,(52)(53)(54), and preliminary findings reported by this study (discussed below) indicated that differential phage predation may be occurring in our mesocosms. However, whether or not this scenario fully applies to our mesocosm incubations remains to be experimentally tested.…”
Section: Discussionsupporting
confidence: 75%
“…Under such stressful conditions, lysogenic bacteriophages can transition to a lytic phase (55)(56)(57). Moreover, the patterns observed might also be attributed, at least partly, to a "kill the winner" scenario (52). Under this scenario, the most successful population, i.e., the one with efficient biodegradation genes under the growth conditions of our mesocosms, is preferentially targeted by bacteriophages.…”
Section: Discussionmentioning
confidence: 94%
“…According to the model proposed by Rodriguez-Valera et al (2009), the increase in abundance of a successful bacterial strain increases the chance of finding a phage specific to that strain (Lotka-Volterra dynamics). In this model, rare genotypes have a fitness advantage over abundant genotypes (i.e., kill-the-winner dynamics).…”
Section: Ecological Speciation With Phagesmentioning
confidence: 99%
“…Several authors have misinterpreted this kind of refutation as equivalent to a radical negation of any role of viruses in cell evolution [66,90]. However, it is important to stress that excluding viruses from the tree of life based on phylogenetic tests does not preclude the major role that viruses have played and still play in the evolution of cellular organisms acting as a strong and dynamic selective pressure on their hosts and fostering a permanent arms race [91]. Viruses are also important actors in cellular evolution by serving as vehicles for gene transfer and as accelerators of gene evolutionary rate ('mutators'), which may lead to punctual innovations that can be returned back to cells.…”
Section: Conclusion: the Vanishing 'Fourth Domain'mentioning
confidence: 99%